Diffuse Alveolar Hemorrhage (DAH) - Murray, John; O’Brien, Shane; Mitchell, Patrick (Seminars in Respiratory and Critical Care Medicine)
Diffuse Alveolar Hemorrhage (DAH) is a life-threatening clinical syndrome characterized by bleeding from the pulmonary microcirculation into alveolar spaces. It typicially presents with acute respiratory failure, anemia, and diffuse radiological infiltrates. Importantly hemoptysis may be absent in up to half of cases. Etiologies are diverse, encompassing systemic vasculitides, connective tissue diseases, coagulopathies, drugs, infections, hemodynamic disturbances, and idiopathic processes. Histopathologically, DAH manifests as one of three overlapping patterns: pulmonary capillaritis, bland alveolar hemorrhage, or diffuse alveolar damage, which help guide diagnostic and therapeutic strategies. Capillaritis, commonly associated with immune-mediated vasculitis such as ANCA-associated vasculitis and anti-glomerular basement membrane disease, typically necessitating prompt and aggressive immunosuppression. In contrast, bland hemorrhage often reflects coagulopathy or hemodynamic factors, while diffuse alveolar damage is linked to toxins, infections, or ARDS. Prompt recognition and systematic evaluation are critical to optimizing outcomes, given DAH’s high in-hospital mortality exceeding 20%. Diagnosis relies on a combination of imaging, bronchoalveolar lavage (demonstrating progressively bloodier returns and hemosiderin-laden macrophages), and targeted laboratory evaluation for vasculitis, infection, and coagulopathy. Management includes patient stabilization with supplementary oxygen or indeed ventilatory support, careful avoidance of ventilator-induced lung injury, and etiology-directed therapy. High-dose corticosteroids, cytotoxic agents, and rituximab remain central in immune-mediated cases, while plasma exchange is indicated in anti-GBM disease and severe refractory hemoptysis. Antimicrobial therapy, drug withdrawal, hemostatic interventions, and, in select cases, extracorporeal support may also be required. This review outlines the histopathological spectrum, etiologic categories, diagnostic algorithms, and evidence-based therapeutic approaches to DAH, emphasizing the importance of early multidisciplinary management to improve survival and functional recovery.